Single-center Study Comparing Short and Mid-Term Results of EVAR in Old and Young Populations - Yalcin,Mihriban (2019)
Abstract Objective: The purpose of this study was to compare the operative mortality rate and outcomes of endovascular aneurysm repair (EVAR) between young and geriatric people in a single center. Methods: Eighty-five patients with abdominal aortic aneurysms who underwent EVAR between January 2012 and September 2016 were included. Outcomes were compared between two groups: the young (aged < 65 years) and the geriatric (aged ≥ 65 years). The primary study outcome was technical success; the secondary endpoints were mortality and secondary interventions. The mean follow-up time was 36 months (3-60 months). Results: The study included 72 males and 13 females with a mean age of 71.08±8.6 years (range 49-85 years). Of the 85 patients analyzed, 18 (21.2%) were under 65 years old and 67 patients (78.8%) were over 65 years old. There was no statistically significant correlation between chronic disease and age. We found no statistically significant difference between aneurysm diameter, neck angle, neck length, or right and left iliac angles. The secondary intervention rate was 7% (six patients). The conversion to open surgery was necessary for only one patient and only three deaths were reported (3.5%). There was no statistically significant difference in the mortality and reintervention rates between the age groups. The three deaths occurred only in the geriatric group and two died secondary to rupture. Kidney failure was observed in three patients in the geriatric group (4.5%). Conclusion: Our single-center experience shows that EVAR can be used safely in both young and geriatric patients.